DEVELOPMENT OF LANGUAGES AND FACTORS OF DEVELOPMENT - Islamova Ezoza Yorkin kizi (TADQIQOTLAR.UZ, 2024)
Abstract. Languages are characterized by very small, isolated groups whose members are very familiar with current events, and who find short and concise sentences sufficient to communicate information, in which verb stems identify subjects and situations. combined with denotative affixes.